Academic Dishonesty from the Perspective of Primary School Teachers - Ferková Štefánia; Zacharová Zlatica (Sciendo, 2024)
Introduction: Academic dishonesty is addressed by various experts in pedagogy and psychology who seek to preserve academic integrity in accordance with the moral and ethical principles of contemporary society.